Analysis of Segmenting, Targeting, And Positioning At PT. Harnawangsa Persada Abadi Sumedang - Nurfonda, Alfi Novia; Amanda, Helles; Karmila, Ila (Journal of Bussines Management Basic, 2025)
This study aims to analyze the application of Segmenting, Targeting, and Positioning in PT. Harnawangsa Persada Abadi Sumedang especially in its business unit Sapphire City Park. The research method used was qualitative descriptive with data collection techniques through observation, interviews, documents, and triangulation of seven research informants. Data analysis was carried out using data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that the segmentation applied by PT. Harnawangsa Persada Abadi Sumedang targets consumers from the inner and outer regions of the city of Sumedang, focusing on the upper middle class without age and gender restrictions, with a healthy and modern lifestyle that likes the outdoors and needs venue services for various types of events. The targeting strategy is focused on individuals, corporations and government agencies as the main target market, by providing a choice of venues, for private events, business activities, and formal events. The positioning strategy is built by creating an image as a venue service provider with a garden view concept that offers a beautiful, comfortable, exclusive, and memorable atmosphere. To improve Segmenting, Targeting and Positioning strategies, companies are advised to optimize digital marketing, make price adjustments, and encourage service innovation.